Analysis of Stones in patients presenting with kidney stone disease: A study from Khairpur - Danwar, Rozina; Balouch, Naeem; Abbas Sahr, Rafeeq (Pakistan Journal of Kidney Diseases, 2024)
The study was comprised of the chemical analysis of certain constituents in the 100 renal calculi samples that were collected from the District Khairpur randomly and the study of the samples was evaluated by the frequency of occurrence on the basis of age and Sex and their morphological composition. A quantitative analysis was derived by the mean of highly sensitive techniques and the ethics was also included. One-hundred calculi samples were obtained from patients admitted in Khairpur Medical college (KMC) and Gambat Institute of Medical Sciences (GIMS) from District Khairpur, upon which 68 were male and 32 were female Urolithaisis patients. The most cases were observed in the age group between 16-30. The calculi samples were subjected for qualitative as well as quantitative analysis, for determination of calcium, phosphorus and oxalate that are the main constituents of the calculi. Morphological examination was also conducted on the basis of color, size, shape and weight.